2020
DOI: 10.15252/embr.202050214
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal lipolysis participates in PUFA‐mediated neural function and neurodegeneration

Abstract: Lipid droplets (LDs) are dynamic cytoplasmic organelles present in most eukaryotic cells. The appearance of LDs in neurons is not usually observed under physiological conditions, but is associated with neural diseases. It remains unclear how LD dynamics is regulated in neurons and how the appearance of LDs affects neuronal functions. We discovered that mutations of two key lipolysis genes atgl‐1 and lid‐1 lead to LD appearance in neurons of Caenorhabditis elegans. This neuronal lipid accumulation protects neur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 61 publications
1
27
0
Order By: Relevance
“…In humans, loss-of-function mutations in DDHD2 lead to hereditary spastic paraplegia [276][277][278] , a neurodegenerative disorder associated with lipid accumulation in the brain and characterized by spasticity in the lower limbs 276 . Putative DDHD2-dependent mechanisms that may underlie hereditary spastic paraplegia include (1) the accrual of LDs, which would hinder protein and/or lipid trafficking required for synapse assembly 276 , (2) reduced cardiolipin biosynthesis and increased ROS production in mitochondria, which would trigger apoptosis of motor neurons in the spinal cord 279 and (3) altered mobilization of FAs from LDs, which would affect membrane phospholipid composition and neuronal function 280 . Additionally, short-hairpin-RNA-mediated DDHD2 knockdown was shown to impair phospholipid synthesis and sensory axon regeneration after sciatic nerve crush 281 , emphasizing a crucial role for lipolysis in neuron function.…”
Section: Carboxyl Esterase Family Members Involved In Lipolysismentioning
confidence: 99%
“…In humans, loss-of-function mutations in DDHD2 lead to hereditary spastic paraplegia [276][277][278] , a neurodegenerative disorder associated with lipid accumulation in the brain and characterized by spasticity in the lower limbs 276 . Putative DDHD2-dependent mechanisms that may underlie hereditary spastic paraplegia include (1) the accrual of LDs, which would hinder protein and/or lipid trafficking required for synapse assembly 276 , (2) reduced cardiolipin biosynthesis and increased ROS production in mitochondria, which would trigger apoptosis of motor neurons in the spinal cord 279 and (3) altered mobilization of FAs from LDs, which would affect membrane phospholipid composition and neuronal function 280 . Additionally, short-hairpin-RNA-mediated DDHD2 knockdown was shown to impair phospholipid synthesis and sensory axon regeneration after sciatic nerve crush 281 , emphasizing a crucial role for lipolysis in neuron function.…”
Section: Carboxyl Esterase Family Members Involved In Lipolysismentioning
confidence: 99%
“…Depletion of HSL1/hosl-1 or ATGL/atgl-1, which are involved in lipid droplet hydrolysis (see Fig. 1m) 24,[56][57][58] , led to an increase in lipid droplet number and a slight but significant lifespan extension (Fig. 2a, b, Extended Data Fig.…”
Section: Mainmentioning
confidence: 97%
“…Cell-intrinsic metabolic processes also make an important contribution towards preventing LDs from accumulating in neurons. For example, neurons express at least two different TAG lipases—ATGL and DDHD2—and their loss-of-function or chemical inhibition can lead to ectopic LDs in mammalian, Drosophila and C. elegans neurons ( Inloes et al, 2014 ; Inloes et al, 2018 ; Yang et al, 2020a ; Wat et al, 2020 ). In C. elegans , it has also been shown that mutations in an Abhydrolase Domain-Containing Protein 5 (ABHD5)/Comparative Gene Identification-58 (CGI-58) orthologue, a known co-activator of ATGL, or overexpression of DGAT1/2 orthologues leads to ectopic LDs in neurons ( Yang et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, neurons express at least two different TAG lipases—ATGL and DDHD2—and their loss-of-function or chemical inhibition can lead to ectopic LDs in mammalian, Drosophila and C. elegans neurons ( Inloes et al, 2014 ; Inloes et al, 2018 ; Yang et al, 2020a ; Wat et al, 2020 ). In C. elegans , it has also been shown that mutations in an Abhydrolase Domain-Containing Protein 5 (ABHD5)/Comparative Gene Identification-58 (CGI-58) orthologue, a known co-activator of ATGL, or overexpression of DGAT1/2 orthologues leads to ectopic LDs in neurons ( Yang et al, 2020a ). Similarly, some perilipins protect LDs from lipolysis, and overexpression of either the Lsd-1 or Lsd-2 perilipins in Drosophila photoreceptors results in a large increase in the usually sparse LDs in these neurons ( Girard et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation